Uji Aplikasi Abu Boiler dan Arang Kayu Sebagai Media Tumbuh Alternatif Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Pembibitan Awal - Aang Kuvaini; Ramayani Br Surbakti (JURNAL CITRA WIDYA EDUKASI, 2019)
The best plant media used in early seeding of oil palm is top soil with a thickness of 10 to 30 cm. Top soil is a layer of soil with high organic content, but at present its availability is rarely found so it needs a solution as its replacement. A alternative is to use organic material ash boiler with wood charcoal. This study aims to determine the effect of ash boiler and wood charcoal as a medium to grow against some indicators of oil palm seed growth. This research was conducted from February to May 2017. The experimental design used was a complete randomized design of one factor, namely P0: 100% sub soil (without wood charcoal and boiler ash), P1: 10% ash boiler + 10% charcoal wood + 80% sub soil, P2: 20% ash boiler + 20% wood charcoal + 60% sub soil, P3: 30% ash boiler + 10% charcoal + 60% sub soil, P4: 10% ash boiler + 30% wood charcoal + 60% sub soil. Each treatment was repeated 2 times, so there were 10 experimental units. Each experimental unit consists of 2 samples. The total number of plants is 20 plants. The result of the research shows that the ash of boiler and charcoal have significant effect on the growth of plant morphology (plant height, stem diameter, number of leaves), and plant physiology (boimassa plant), but no significant effect on leaf area parameters.